2015
DOI: 10.3329/bjar.v40i1.23769
|View full text |Cite
|
Sign up to set email alerts
|

Determination of maturity indices of BER (Zizyphus mauritiana Lam.) Var. BARI Kul-2

Abstract: A study was conducted at Fruit Research Farm and Postharvest Technology Laboratory of Horticulture Research Centre, Bangladesh Agricultural Research Institute during the period from October 2009 to February 2010 to determine the maturity indices of ber. The ber variety BARI Kul-2 was selected for conducting the study. Ber fruits were tagged at fruit setting stage and harvested at 90, 100, 110, 120 days after fruit set (treatments). The physicochemical characters like fruit weight and size, specific gravity, TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
3
3
0
Order By: Relevance
“…4) and can be used for processing and table purpose. The results are in line with the findings of Islam et al [22].…”
Section: Organoleptic Scoresupporting
confidence: 93%
“…4) and can be used for processing and table purpose. The results are in line with the findings of Islam et al [22].…”
Section: Organoleptic Scoresupporting
confidence: 93%
“…1.2) after fruit setting, which might be due to the reason that available organic acids utilized at faster rate during the respiratory process (Bal et al, 1995) [2] . Similar observation was reported by Islam et al, (2015) [5] who reported that total acidity decreased gradually from 90 days to 130 days of ber fruit setting. [11] who observed an increasing trend in ascorbic acid content of cultivar Mehrun-khedi, Mehrun and M.P.K.V.…”
Section: Aciditysupporting
confidence: 88%
“…Then, a one-way ANOVA was performed to see how temperature affected the parameters of the enzyme kinetic model using SYSTAT 13.2v (Mangaraj et al, 2021). The impact of storage days on each of the apple's quality features during storage using the MAP technique was then statistically assessed by Duncan's multiple range test (DMRT) using SAS 9.3v software (Islam et al, 2015).…”
Section: Discussionmentioning
confidence: 99%